Comparison of prognosis of patients with endometrial cancer after hysteroscopy versus dilatation and curettage: A multicenter retrospective study - Liu, Shihuang; Zhen, Lan; Zhang, Shaoyu; Cai, Yurong; Lin, Yanying; Chen, Fulian; Li, Xiaowen; You, Qianru; Lai, Xiaohong; Lai, Hangbo; Zheng, Xiangqin; Yi, Huan (Frontiers in Medicine, 2023)
Introduction: Hysteroscopy is a useful procedure for diagnosing endometrial cancer. There is controversy regarding whether hysteroscopy affects the prognosis of endometrial cancer by prompting cancer cell into intraperitoneal dissemination. Our purpose was to confirm whether hysteroscopy could be a risk factor of the tumor stage, recurrence and survival rate of endometrial cancer. Methods: This multicenter retrospective study included all consecutive patients who had endometrial carcinoma diagnosed preoperatively with hysteroscopy and directed endometrial biopsy (HSC, group A) and dilatation and curettage (D&C, group B) between February 2014 and December 2018 at the Fujian Provincial, China. We compared the demographic feature, clinical characteristics and prognosis between the two groups. Result: A total of 429 patients were included in the study (Group A, n=77; Group B, n=352). There was no significant difference between their baseline characteristics [including age, BMI, histological type and International Federation of Gynecology and Obstetrics (FIGO) stage]. By comparing several pathological conditions that may affect prognosis, there were no significant differences between the two groups in the peritoneal cytology, depth of myometrial invasion, the positivity of lymph nodes, lymphovascular space invasion and paraaortic lymph node dissection. Finally, no significant difference was found between the two groups in overall survival (OS) (P=0.189) or recurrence free survival (RFS) (P=0.787). Conclusion: Under certain inflation pressure and distension medium, hysteroscopic examination and lesion biopsy ensure the safety and have no adverse effects on prognosis compared to conventional curettage.